Identifikasi Kandungan Konsentrat Mineral Logam Pada Tailing Penambangan Emas Rakyat - Noveriady Noveriady; Novalisae Novalisae; I Putu Putrawiyanta; Ferdinandus Ferdinandus (Universitas Islam Raden Rahmat, Malang, 2025)
Artisanal gold mining in the Kahayan River Basin (DAS Kahayan), Ramang Village, produces tailings that contain metallic minerals such as zircon (Zr), yet their management remains suboptimal. This study aims to identify the zircon content in the concentrate resulting from shaking table separation and to analyze the geological and hydrological factors influencing its distribution. The results show that zircon content in the tailings ranges from 0,002% to 0,112%. The highest concentration was found in the upstream area (Z1), while the lowest was in the downstream area (X1), indicating that river flow direction and tidal influences play a role in zircon particle distribution. The zircon identified is genetically linked to the weathering of granite rocks, particularly the Kapur Granite Formation and Sepauk Tonalite in the upstream region. These findings indicate that current small-scale gold mining practices remain inefficient, allowing zircon to be discarded in tailings. This study emphasizes the importance of improved tailings management through efficient containment systems, the potential for reprocessing, and continuous environmental monitoring to enhance resource utilization and reduce the ecological impact of traditional mining.